The Nature of the Spectacle On Images, Money, and Conserving Capitalism - Igoe, Jim (University of Arizona Press, 2021)
Today crisis appears to be the normal order of things. We seem to be turning in widening gyres of economic failure, species extinction, resource scarcity, war, and climate change. These crises are interconnected ecologically, economically, and politically. Just as importantly, they are connected-and disconnected-in our imaginations. Public imaginations are possibly the most important stage on which crises are played out, for these views determine how the problems are perceived and what solutions are offered.In The Nature of Spectacle, Jim Igoe embarks on multifaceted explorations of how we imagine nature and how nature shapes our imaginations. The book traces spectacular productions of imagined nature across time and space-from African nature tourism to transnational policy events to green consumer appeals in which the push of a virtual button appears to initiate a chain of events resulting in the protection of polar bears in the Arctic or jaguars in the Amazon rainforest. These explorations illuminate the often surprising intersections of consumerism, entertainment, and environmental policy. They show how these intersections figure in a strengthening and problematic policy consensus in which economic growth and ecosystem health are cast as mutually necessitating conditions. They also take seriously the potential of these intersections and how they may facilitate other alignments and imaginings that may become the basis of alternatives to our current socioecological predicaments.